2017
DOI: 10.1097/md.0000000000005746
|View full text |Cite
|
Sign up to set email alerts
|

Conditional disease-free survival among patients with breast cancer

Abstract: Conditional disease-free survival (CDFS) reflects changes over time. Because traditional disease-free survival (DFS) is estimated from the date of diagnosis, it is limited in the ability to predict risk of recurrence in patients who have been disease free. In this study, we determined CDFS of breast cancer patients and estimated the prognostic factors for DFS.We retrospectively reviewed clinical data of 7587 consecutive patients who underwent curative surgery for breast cancer between January 2004 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…By comparison, stage III MCs were associated with a +27% gain in CSS in dogs from diagnosis to 12 months after, whereas in cats stage III MCs showed also a relatively stable CSS probability over time (+5% gain in CSS from diagnosis to 12 months after); in both species, cancer stage still impacted CSS in 12‐month survivors. These observations in dogs correlate with those reported in human breast cancer, in which lower stages do not significantly affect the relative CS, whereas women with higher‐stage breast cancers have a significant improvement of their relative CS if they have survived 5 years 42‐45,55,56 . In other words, the more advanced stage at diagnosis, the more survival time means “good news” for the patient, that is, decreased probability of dying from cancer afterwards.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…By comparison, stage III MCs were associated with a +27% gain in CSS in dogs from diagnosis to 12 months after, whereas in cats stage III MCs showed also a relatively stable CSS probability over time (+5% gain in CSS from diagnosis to 12 months after); in both species, cancer stage still impacted CSS in 12‐month survivors. These observations in dogs correlate with those reported in human breast cancer, in which lower stages do not significantly affect the relative CS, whereas women with higher‐stage breast cancers have a significant improvement of their relative CS if they have survived 5 years 42‐45,55,56 . In other words, the more advanced stage at diagnosis, the more survival time means “good news” for the patient, that is, decreased probability of dying from cancer afterwards.…”
Section: Discussionsupporting
confidence: 84%
“…Afterwards, Ki‐67 was not significantly associated with CSS because there had been a +25% gain in CSS in 12 months for highly proliferative MCs. In women with breast cancer, the Ki‐67 proliferation index (at 14% cut‐off) is not significantly associated with relative CS of 5‐year surviving patients 56 …”
Section: Discussionmentioning
confidence: 88%
“…A study investigating conditional disease-free survival in relation to subtype also showed that ER- tumors conditional DFS improved but suggested that conditional survival decreased for ER+ tumors. This study was limited by a very small number of patients at risk after more than three disease-free years [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In only a few CEAs, the methodology of cost abstraction and data abstraction were not clear, which may be because these publications were performed in local settings, so there might have been an assumption that the health-care settings were already familiar with these parameters. All the studies were performed with an appropriate time horizon starting from 5 years, which is also used to estimate disease-free survival in breast cancer in some clinical studies [52]; only one study was conducted over a time horizon of 3 years [25], which may be assumed non-sufficient.…”
Section: Discussionmentioning
confidence: 99%